EFEKTIVITAS TUGAS TIM EVALUASI DAN PENGAWASAN PENYERAPAN ANGGARAN (Studi di Biro Administrasi Pembangunan dan Sumber Daya Alam Sekretariat Daerah Provinsi Sulawesi Tengah) - Wahyuni, Ita (Katalogis, 2015)
This reseacrh aims at figuring out and analyzing the task effectiveness of evaluation team and budget absorption control at Bureau of Development Administration and Natural Resources of Regional Secretariat, Central Sulawesi. This is a qualitative research with descriptive method. The informants of this research are the employees of Bureau of Development Administration and Natural Resources of Regional Secretariat, Central Sulawesi that taken purposively. The techniques of the data analysis refers to yhe stages of Miles and huberman which consist of three simultaneous activities namely data reduction, data presentation, and verification. The research results show that the evaluation team and budget absorption control at Bureau of Development Administration and Natural Resources of Regional Secretariat, central Sulawesi did not work effectivelly due to some problems in the process of budget absorbing such as schedule delays, delays in the disbursement of funds, auction delays, delays of decree of technical enforcement officials/treasurer and the delays of RKA/DPA.